SEGMENTASI CITRA MEDIS UNTUK PENGENALAN OBJEK KANKER MENGGUNAKAN METODE ACTIVE CONTOUR - Fatkhurrazi Basyid; Kusworo Adi (Youngster Physics Journal, 2014)
Cancer diseases characterized by abnormal cell cycle, in which the body cells grow out of control (cell division beyond the normal limits) and invade nearby healthy tissue. Cancer cells are actively dividing sensitive to radiation exposure, so that cancer can be treated with a high dose of radiation that is commonly referred to radiotherapy. High-dose radiation is damaging tissue, therefore radiotherapy should be planned carefully. Dose in cancer cells should be precise and dangerous organs (organs at risk) should not receive high doses. Contouring is the process of determining the volume of cancer and other organs at risk. Research on contouring is done by developing a step-by-step algorithm that is able to localize the area detected as cancer and also borders cancer, so it is visually identifiable characteristics and forms of cancer. Active contour image segmentation methods used to separate and identify cancer cells with healthy cells. Active contour is able to recognize the limits of automatic edge, so as to know the boundary between cancer cells with healthy cells. Determination of volume and visualization of cancer is done by segmenting the image of each piece, then each piece of the image reconstruction process is carried out to obtain the volume visualization of cancer and dangerous organ in three dimensions. The results showed that the active contour segmentation method can perform image segmentation for multi-region with objects, objects that are close together but are sensitive to image noises.Keywords : cancer, radiotherapy, segmentation, active contour